1994
DOI: 10.1016/0277-9536(94)90281-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic job insecurity among automobile workers: Effects on job satisfaction and health

Abstract: Work conditions characterized by uncertainty and ambiguity are potential stressors for employees. One such stressor is job insecurity. This longitudinal study of 207 automobile manufacturing workers indicates that chronic job insecurity is predictive of changes over time in both job satisfaction and physical symptoms. Extended periods of job insecurity decrease job satisfaction and increase physical symptomatology, over and above the effects of job insecurity at any single point in time. These results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
243
0
18

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(274 citation statements)
references
References 18 publications
13
243
0
18
Order By: Relevance
“…Previous studies have shown that chronic job insecurity leads to poor selfrated health, a severely increased risk of minor psychiatric morbidity and premature mortality (e.g. Burgard et al 2012;Ferrie 2001;Heaney et al 1994;House et al 1986). As the chronic nature of job insecurity continues unabated, the stressor might consume the employee's resources, and hence, it jeopardizes the use of effective and appropriate coping strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that chronic job insecurity leads to poor selfrated health, a severely increased risk of minor psychiatric morbidity and premature mortality (e.g. Burgard et al 2012;Ferrie 2001;Heaney et al 1994;House et al 1986). As the chronic nature of job insecurity continues unabated, the stressor might consume the employee's resources, and hence, it jeopardizes the use of effective and appropriate coping strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Because the specific date in the transitional period when the person became unemployed was not measured by the census, this period contained time prior to the person becoming unemployed and the time during a period of unemployment. Since concern about job loss may have adverse health effects (28)(29)(30) and the earliest period of unemployment may have acute effects on health and on health care behavior, we separated this period from the "during unemployment" Table 1. Classification of health care use by period of unemploym period.…”
Section: Methodsmentioning
confidence: 99%
“…Job insecurity refers to employees' perceptions and concerns about potential involuntary job loss (De Witte 1999;Heaney et al 1994). Greenhalgh & Rosenblatt (1984) define job insecurity as a perceived powerlessness to maintain desired continuity in a threatened job situation.…”
Section: National Institute Of Occupational Safety and Health (Niosh)mentioning
confidence: 99%